ACADEMIC PROCRATINATION OF STUDENTS POST PANDEMIC COVID-19 - Adnan Fadkhurosi; Muhammad Ramadhan; Mashurin (Program Studi Bimbingan dan Konseling, 2023)
The research aims to determine the level of academic procrastination of Solo students after the Covid-19 pandemic. The research method used was a quantitative survey with a population of 35,000 and a sample of 268 students. The data sampling technique uses simple random sampling, so that the sample used will be fair and impartial. The data analysis technique used was descriptive analysis, which was processed through the IBM SPPS 22 application. The results of the study revealed that the majority of Solo students were moderately procrastinated or 75.7% equivalent to 203 of the 268 student samples. The results of the procrastination survey are supported by the average results of aspects that support procrastination, namely aspects of desire and action, aspects of failing to meet the specified time, aspects of self-ability, and aspects of feelings of anxiety. These aspects show that the average student tends to moderate academic procrastination after the Covid-19 pandemic. This research can be used as a reference for further research in order to develop relevant knowledge.